2009
DOI: 10.1007/s00106-009-2019-8
|View full text |Cite
|
Sign up to set email alerts
|

Ablenkungs- und Entspannungstraining bei akutem Tinnitus

Abstract: In acute tinnitus, distraction and relaxation training should be conducted as a complement to standard medical treatment, especially in high-risk patients demonstrating abnormal psychopathological status, since treatment results can be improved in this way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, none of these treatment methods have proven to be effective after replication in controlled trials (Elgoyhen and Langguth, 2011 ). On the other hand, different types of psychotherapeutic intervention supporting and accompanying medical treatment have also been designed (Schildt et al, 2006 ; Gerhards and Brehmer, 2010 ). These adjuvant psychotherapeutic interventions consist of one or more of the following elements: psycho-educative counseling, relaxation training, and general and tinnitus-related stress management.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of these treatment methods have proven to be effective after replication in controlled trials (Elgoyhen and Langguth, 2011 ). On the other hand, different types of psychotherapeutic intervention supporting and accompanying medical treatment have also been designed (Schildt et al, 2006 ; Gerhards and Brehmer, 2010 ). These adjuvant psychotherapeutic interventions consist of one or more of the following elements: psycho-educative counseling, relaxation training, and general and tinnitus-related stress management.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that a single approach might not be as effective as a combined approach similar to what we applied in our research presented here. This is underpinned by several researchers who proposed the use of sound with educational elements and stress-reduction techniques supplemented with psychological and medical management as the most promising way to treat tinnitus [ 9 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that tinnitus symptoms are widespread and individually different integrative approaches in treating tinnitus have been proposed. These include cognitive-behavioral treatment (CBT) [ 8 ], relaxation techniques [ 9 ] as well as sound therapeutic options to reduce the acoustic symptoms and are regarded as promising for managing tinnitus [ 10 ]. A recent review of 31 studies [ 11 ] found multidisciplinary CBT-based tinnitus treatment the most promising option for treating patients with tinnitus.…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive task provided a distraction for subjects meaning they did not attend to low sound levels in the room. Treatment and intervention measures for tinnitus often work on developing distraction techniques to assist sufferers [15].…”
Section: Background and Related Research A Tinnitus Related Behamentioning
confidence: 99%